Risk and Change Order Impact Analysis of Costs in Tamansari Iswara Bekasi Project - Sunandar, Ali; Aszhari, Kuncoro Bili (Quantitative Economics and Management Studies, 2021)
In every construction project, there is always a change or what is commonly called a change order (CO). CO greatly affects the effectiveness of project work where its sustainability depends on three interrelated components namely quality, time and cost. The purpose of this study is to determine the causes, risks, impact of CO and risk management on costs. This research was conducted in the Bekasi area at the Tamansari Iswara project. This study uses descriptive analysis methods and direct interviews with the experts concerned by distributing questionnaires to 85 respondents and producing data for analysis. With the help of statistical analysis software that is SPSS researchers use several tests such as validity test, reliability test, descriptive analysis test, regression analysis, and risk analysis to determine the dominant variables and risk management. From the results of the analysis conducted there are 6 dominant variables namely X18, X19, X15, X28, X21, X9, X25, and the highest risk is found in variables X1 and X21.